Diagnostic applications of health intelligence and surveillance systems - Yadav, Divakar, 1976-; Bansal, Abhay; Bhatia, Madhulika, 1984-; Hooda, Madhurima, 1985-; Morato, Jorge, 1967- (Advances in medical technologies and clinical practice book series., 2021)
"The book is a great reference about the various application and scientific work going on in this area of how AI is driving the Health sector and helping health practitioners to predict disease intensity using the latest technology"--